Expression of Metabolic Coupling and Adhesion Proteins in the Porcine Optic-Nerve Head: Relevance to a Flow Model of Glaucoma - Carreras, Francisco-Javier; Porcel, David; Rodriguez-Hurtado, Francisco; Zarzuelo, Antonio; Carreras, Ignacio; Galisteo, Milagros (IntechOpen, 2011)
None